5
$\begingroup$

Suppose $x_1, x_2, x_3,\ldots, x_n$ are i.i.d. random variables with a common Poisson$(\lambda)$ distribution.

I was trying to find an unbiased estimator for $\lambda(1 - e^\lambda)$, but I could not find any. Is there a way to prove that there is not any unbiased estimator for $\lambda(1 - e^\lambda)$ ?

$\endgroup$
  • 3
    $\begingroup$ Here is a MathJax tutorial for typesetting math here. And if this is homework, do add the self-study tag. $\endgroup$ – StubbornAtom Mar 11 at 16:33
  • $\begingroup$ @beta1_equals_beta2 Let the OP clarify. $\endgroup$ – StubbornAtom Mar 11 at 16:46
12
$\begingroup$

Actually, an unbiased estimator does exist. Let us define $\tau = \lambda e^\lambda$ so that $$\lambda(1-e^\lambda) = \lambda - \tau$$ Since the sample mean $\bar{X}$ is unbiased for $\lambda$, really all we need is an unbiased estimator for $\tau$. An obvious starting place is to use the invariance property of the MLE. $$\hat\tau_\text{mle} = \bar{X}e^\bar{X}$$ For reasons which will shortly become clear, let's adjust this estimator by introducing a quantity $m$ in the exponential term.

$$\hat\tau_m = \frac{T}{n}e^{T/m}$$ where $T = \sum_{i=1}^n X_i$ has a $\text{Poisson}(n\lambda)$ distribution. The expected value of $\hat\tau_m$ can be found directly.

\begin{aligned} E(\hat\tau_m) &= \sum_{t=0}^\infty \left(\frac{t}{n}e^{t/m}\right)\left(\frac{e^{-n\lambda}(n\lambda)^t}{t!}\right) \\[1.2ex] &= \cdots && \text{show this on your own} \\[1.2ex] &= \lambda\left(e^{\lambda(e^{1/m} - 1)n}\right)e^{1/m} \end{aligned}

This estimator is clearly biased (for now). To make this an unbiased estimator, we need $(e^{1/m}-1)n = 1$ for all $n$. Solving this equation, we obtain $m_\star = (\log(1+1/n))^{-1}$. Using this value for $m$ yeilds, $$E(\hat\tau_{m_\star}) = \frac{\lambda e^\lambda}{1+1/n}$$ I'll leave the rest of the details up to you, but this estimator can now be adjusted so that it is unbiased for $\tau$.

$\endgroup$
  • $\begingroup$ I tried calculating E( that _m) . For t=0 the sum is zero , thus I took the sum t=1 to infinity , then after some calculations I wanted to set (y=t-1) to use the summation formula of e^λ but i am not sure how . So i got the following: E( that _m) = λ e^(-nλ) Σ e^(t/m) [(nλ)^t-1]/ (t-1)! at this point I am not sure what to do . I am trying to write e^(t/m) as e^(t-1) so that I can use the formula ( e^λ = Σ(0 to infinity) (λ^x) / x! ) but I am not sure how $\endgroup$ – GAGA Mar 12 at 6:44
  • 1
    $\begingroup$ In your first comment, you are nearly there. When you set $y=t-1$, the sum in your comment becomes $\sum_{y=0}^\infty e^{(y+1)/m}(n\lambda)^y/y!$. You can pull out a $e^{1/m}$ and obtain $(e^{1/m}n\lambda)^y$ in the numerator. $\endgroup$ – knrumsey Mar 12 at 16:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.